Organization of Icebreaking Conducting of Transport Courts - Aleksei Vasilievich Abramov; Mikhail Aleksandrovich Zagorodnikov (Управленческое консультирование)
Various making tactics of transportation of freights on Northern Sea Route are given in article. Offers on distribution of innovative ice breakers on routes Northern Sea Route are given.